Perawatan Dan Perbaikan Sistem Hidrolik Excavator Zaxis 110 - M - Khairunnisa Khairunnisa; Ismael Ismael; Muh Anhar (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Excavators are heavy equipment commonly used in projects such as bridge construction and land clearing. In the hydraulic system of an excavator, there are components such as the main pump, regulator pump, control valve, and pilot valve, which function to supply power that will then be converted to actuator components such as the swing motor, track link, boom, arm, and bucket. Improper maintenance scheduling can lead to unpredictable time and cost losses.In conducting this research, the author used several methods to obtain the necessary data, including surveys, interviews, and discussions with mechanics.The type of maintenance carried out at BAPPEDA of the Ketapang Regency Research and Development Agency Regency is Breakdown Maintenance. Maintenance planning is always prepared at the beginning of the year and then documented at the end of the year. Preventive maintenance is only conducted to assess the condition of components and to prepare for necessary repairs. Repairs are carried out based on the planned maintenance schedule as well as unexpected damage that occurs in the field. With proper maintenance scheduling, it is expected to have a positive impact on the service life of several components in the excavator's hydraulic system.